Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of display size and navigation type on a classification task

Abstract: The advent of ultra-high resolution wall-size displays and their use for complex tasks require a more systematic analysis and deeper understanding of their advantages and drawbacks compared with desktop monitors. While previous work has mostly addressed search, visualization and sense-making tasks, we have designed an abstract classification task that involves explicit data manipulation. Based on our observations of real uses of a wall display, this task represents a large category of applications. We report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 23 publications
4
109
3
1
Order By: Relevance
“…For instance, arranging multiple visualizations side-by-side can allow for faster and easier comparison than navigating between multiple components on a single abstract interface; the user can easily switch views using physical head or body motion and apply spatial memory to recall the location of important items, making for an efficient and intuitive experience. Several research studies have shown examples where interfaces that leverage motion in space over large displays [126,186], multiple displays [21,190] or through virtual navigation [38,121] can provide more efficient navigation or improved understanding of complex tasks.…”
mentioning
confidence: 99%
“…For instance, arranging multiple visualizations side-by-side can allow for faster and easier comparison than navigating between multiple components on a single abstract interface; the user can easily switch views using physical head or body motion and apply spatial memory to recall the location of important items, making for an efficient and intuitive experience. Several research studies have shown examples where interfaces that leverage motion in space over large displays [126,186], multiple displays [21,190] or through virtual navigation [38,121] can provide more efficient navigation or improved understanding of complex tasks.…”
mentioning
confidence: 99%
“…Kuikkaniemi et al [4] propose a system using direct touch for presentations in public settings. In contrast, Liu et al [6] used a remote touch pad for data manipulation. Zadow et al [13] proposed to use a touch display mounted to user's arm in addition to direct touch.…”
Section: Appropriate Input Techniques Depending On Context Of Usementioning
confidence: 99%
“…In addition, Liu et al [22] compare physical navigation in a wall in contrast with a virtual navigation in a desktop for data manipulation tasks by means of quantitative parameters, such as task completion or physical movements of the participants in front of the wall. Unlike this work, we are interested in obtaining a metric which gives a relation between hardware performance and user satisfaction.…”
Section: Background Of Cluster Visualization Systemsmentioning
confidence: 99%